Cerebral ischemia and dementia: [International Symposium on Cerebral Ischemia and Dementia held in Prien, Chiemsee, in June 1990] - Hartmann, Alexander; Kuschinsky, Wolfgang; Hoyer, Siegfried (Springer Berlin Heidelberg, 1991)
In contrast to dementia of the Alzheimer type, the subject of dementia subsequent to cerebral ischemia has been discussed rather rarely. Now this book provides a summary of the brain morphology, neurochemistry and clinical aspects of dementia subsequent to cerebral ischemia. The contributions discuss the similarities and differences between the two predominant dementia types. The broad range of aspects cover 1) the morphology and morphobiology of brain tissue during aging and under the two pathological condi- tions, 2) the neuropathochemistry of post mortem brain tissue of patients as well as brain tissue from experimental animals, 3) CSF changes during aging and in dementia states and 4) clinical research, mainly using brain imaging tech- niques to differentiate between dementia types and to find a basis for rational therapeutic approaches
Keywords: Konferenzschrift -- 1990 -- Prien, Chiemsee; Demenz; Ischämie; Hirnkrankheit